Pengaruh Pengetahuan Sanitasi Higiene Terhadap Perilaku Kebersihan Siswa Smk Program Keahlian Kuliner Dalam Praktik Pengolahan Makanan - Atika Salsabila A.; Mauren Gita Miranti; Lucia Tri Pangesthi; Lilis Sulandari (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Hygiene in the food sector cannot be separated from the application of hygienic sanitation and hygiene behavior. However, the observation results show that there are still students who have not properly applied food hygiene sanitation knowledge when processing food. The purpose of this study was to find out 1) an overview of students' food hygiene sanitation knowledge, 2) an overview of students' hygiene behavior in food processing practices, and 3) the effect of food hygiene sanitation knowledge on students' hygiene behavior. The research used is descriptive evaluative quantitative research. The instrument used was a questionnaire in the form of multiple choice questions and observation sheets. Knowledge test is used to measure the level of students' knowledge. While the observation is to see students' hygiene behavior when practicing food processing. The analysis technique uses regression. The results showed 1) knowledge of sanitation hygiene 6 students (9.1%) were in the medium category, 37 students (56.1%) were in the good category, and 23 students (34.8%) were in the very good category, 2) behavior cleanliness of 1 student is in the good category and 65 students (98.48%) are in the very good category, 3) hygiene sanitation knowledge affects students' hygiene behavior when practicing food processing with a large influence on the R Square value of 0.115 or 11.5 %. This research implies that sanitary hygiene is applied to every subject. 2) the hygiene behavior of 1 student is in the good category and 65 students (98.48%) are in the very good category, 3) hygiene sanitation knowledge influences students' hygiene behavior when practicing food processing with a large influence on the R Square value of 0.115 or equal to 11.5%. This research implies that sanitary hygiene is applied to every subject. 2) the hygiene behavior of 1 student is in the good category and 65 students (98.48%) are in the very good category, 3) hygiene sanitation knowledge influences students' hygiene behavior when practicing food processing with a large influence on the R Square value of 0.115 or equal to 11.5%. This research implies that sanitary hygiene is applied to every subject.